Answer:
C) H₂PO₄⁻(aq) + H₂O(l) → H₃O⁺(aq) + HPO₄²⁻(aq)
Step-by-step explanation:
For which of the following equilibria does Kc correspond to the acid-dissociation constant, Ka, of H₂PO₄⁻?
A) H₂PO₄⁻(aq) + H₃O⁺(aq) → H₃PO₄(aq) + H₂O(l)
NO. This is the inverse of the acid dissociation of H₃PO₄.
B) H₂PO₄⁻(aq) + H₂O(l) → H₃PO₄(aq) + OH⁻(aq)
NO. This is the basic dissociation of H₂PO₄⁻.
C) H₂PO₄⁻(aq) + H₂O(l) → H₃O⁺(aq) + HPO₄²⁻(aq)
YES. This is the acid dissociation of H₂PO₄⁻. The acid-dissociation constant is:
![Ka=([H_(3)O^(+)].[HPO_(4)^(2-) ])/([H_(2)PO_(4)^(-) ])](https://img.qammunity.org/2020/formulas/chemistry/college/xpc0a5jn4un4x5z9oi6srwc4ahc2vs14ay.png)
D) H₃PO₄(aq) + H₂O(l) → H₃O⁺(aq) + H₂PO₄⁻(aq)
No. This is the acid dissociation of H₃PO₄.
E) HPO₄²⁻(aq) + H₂O(l) → H₂PO₄⁻(aq) + OH⁻(aq)
NO. This is the basic dissociation of HPO₄²⁻.